Genetic polymorphisms in a Colombian women population with breast cancer and tamoxifen consumption - Uribe Echeverrry, Paula Tatiana; Pérez Agudelo, Juan Manuel; Forero Rodríguez, María Angélica; Betancur Pérez, Jhon Fredy (Revista Cubana de Farmacia, 2023)
Introduction: Breast cancer is positioned as the malignancy with the highest prevalence worldwide. In 2022, 2.2 million cases were reported. Colombia is considered the second country with the most frequent numbers of cancer in women. The epidemiological importance of this condition generates the need to establish in the region processes of demographic and clinical characterization, pharmacological intervention and identification of genetic variants, which determine a better understanding of cancer as a multifactorial situation. Objective: To identify single nucleotide polymorphisms of CYP2D6*3, CYP2D*4 and ABCB1 C3435T in women with breast cancer with a history of tamoxifen consumption in the province of Caldas. Methods: A descriptive and retrospective cross-sectional study was conducted in which 49 women from the department of Caldas, diagnosed with breast cancer on treatment with tamoxifen or aromatase inhibitors, who had a blood sample taken under the principles of bioethics and established biosafety criteria and protocols. Subsequently, DNA extraction was performed, followed by amplification of the CYP2D6 *3,*4 and ABCB1 (C3435T) alleles. The digestion of each of the alleles was completed with the restriction enzymes Mspl, MvaI and MboI, respectively. Results: The CYP2D6*3 allele showed no polymorphisms in the analyzed population. The allele of the CYP2D6*4 gene presented polymorphism in the analyzed population: 78% were characterized as wild alleles (*1/*1) and 22% heterozygous alleles (*1/*4). 55.1% heterozygous alleles (TC) and 44.9% mutant homozygous alleles (TT) of the ABCB1 gene were found. Conclusions: The alleles of the CYP2D6*4 gene were heterozygous in the population, finding association with intermediate or deficient metabolism, while not giving the adequate response to tamoxifen consumption, which led to the risk of breast cancer recurrence. The differences in the allelic frequencies of the ABCB1 gene suggest that half of the population analyzed presents the mutation and alteration in the membrane protein.